Strategic Management Analysis on Sharia Cooperative Problems in South Kalimantan in the Digital Era - Naimah, Naimah; Zahra Maulida, Atika; Mahfuzah, Annisa (Tasharruf: Journal Economics and Business of Islam, 2024)
Entering the era of globalization, paradigm transformations in the world of internet, telecommunications, and mobile technology have a tremendous impact on the business world, including one of the areas that must be expanded and exploited optimally: cooperatives that assist low- and middle-income residents. There is a shift in cooperative management strategies employing digital transactions by adopting the following SWOT analysis: 1) the existence of digital transactions in Sharia cooperatives reduces money loans through loan sharks, 2) digital services are easy to understand and implement, transactions may be made anywhere and anytime, 3) lack of human resources who understand digital transactions, 4) ecosystem expansion and digitization in the financial sector, and 5) digital cybersecurity threats that can jeopardize both data and cooperative reputation. This research approach is a qualitative analysis using field-based interview standards. Data was collected using a purposive sampling strategy, with informants selected from Sharia cooperative managers, consumers, and directors. Strengths, weaknesses, threats, and opportunities were identified using SWOT analysis based on the interview data. The outcome of this study is the growth of sharia cooperatives in South Kalimantan, which face both internal and external challenges. These include a lack of human resources, the accessibility of digital-era infrastructure, cooperative management, the types of businesses and products that are offered, product marketing, cooperative institutions, and banking administration management. Based on the study's findings, the researcher came to the conclusion that applying the digital age to Sharia cooperatives has strengths, weaknesses, opportunities, and threats. These include assessing the community's needs, developing strategies and techniques for achieving cooperative goals, creating budgets and programs, and monitoring and managing the digital economic transformation applied to sharia cooperatives.